2005
DOI: 10.1111/j.1550-7408.2005.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

The New Higher Level Classification of Eukaryotes with Emphasis on the Taxonomy of Protists

Abstract: ABSTRACT. This revision of the classification of unicellular eukaryotes updates that of Levine et al. (1980) for the protozoa and expands it to include other protists. Whereas the previous revision was primarily to incorporate the results of ultrastructural studies, this revision incorporates results from both ultrastructural research since 1980 and molecular phylogenetic studies. We propose a scheme that is based on nameless ranked systematics. The vocabulary of the taxonomy is updated, particularly to clarif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
1,049
5
40

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,491 publications
(1,133 citation statements)
references
References 110 publications
16
1,049
5
40
Order By: Relevance
“…Originally, the genus Rozella was placed into the Chytridiomycota, and specifically within the Spizellomycota, where it was classified inside the family Olpidiaceae (Adl et al 2005). Its placement inside chytrids was partly justified on the basis of plesiomorphic characters, such as the existence of a flagellated stage (James et al 2006a).…”
Section: Resultsmentioning
confidence: 99%
“…Originally, the genus Rozella was placed into the Chytridiomycota, and specifically within the Spizellomycota, where it was classified inside the family Olpidiaceae (Adl et al 2005). Its placement inside chytrids was partly justified on the basis of plesiomorphic characters, such as the existence of a flagellated stage (James et al 2006a).…”
Section: Resultsmentioning
confidence: 99%
“…Other sequences belonging to the Silicofilosea were introduced into the analysis; the Thaumatomonadida being used as outgroups in the phylogenetic analyses. This order is considered as the sister-group of the Euglyphida (Adl et al 2005). The highly divergent sequence Tracheleuglypha dentata was not taken into account in the analysis because the branch it formed with rest of the Euglyphida was significantly longer than the other branches and perturbed the analyses; the topology of the tree was identical, but nodes were less supported; T. dentata appeared at the base of the group formed by Trinematidae and Euglypha (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…The eukaryotic super-group Rhizaria (Adl et al 2005) is a large assemblage of morphologically and ecologically dissimilar organisms, comprising both flagellate and amoeboid forms. They can be phagotrophic, secondarily phototrophic (like the Chlorarachniophyta) or parasitic (such as the Haplosporidia and the Plasmodiophorida).…”
Section: Introductionmentioning
confidence: 99%
“…Based on morphological, biochemical, and molecular phylogenetic approaches, eukaryotes have recently been classified into six supergroups: the Opisthokonta, including animals and fungi; the Amoebozoa, including most traditional amoebae and slime moulds; the Excavata, grouping diplomonads, several genera of heterotrophic flagellates, and possibly the Euglenozoa; the Rhizaria, including the Foraminifera and the Cercozoa; the Archaeplastida, grouping red algae, green algae, and plants; and the Chromalveolata, including dinoflagellates, apicomplexan parasites, and the Stramenopiles (brown algae, diatoms, and many zoosporic fungi) (Adl et al 2005;Medina 2005). In order to evaluate the phyletic distribution of the RNAi machinery components, we have surveyed 25 complete or near-complete genomes that belong to five eukaryotic supergroups (with only Rhizaria remaining unsampled).…”
Section: Distribution Of Argonaute-piwi Dicer-like and Rdrp Proteinmentioning
confidence: 99%
“…The relationship among the supergroups, the potential lack of monophyly of Chromalveolata and Excavata, and the placement of the root of the tree have remained contentious (Adl et al 2005;Simpson and Roger 2004). Earlier phylogenetic analyses indicated that diplomonads (including G. intestinalis) are among the deepest divergences in the eukaryotic lineage and the tree was (EAL73658); Gi Dcl1 G. intestinalis Dcl1 (AAO17549); Hs Dcr1 H. sapiens Dcr1 (NP_803187); Ps Dcl1 P. sojae Dcl1 (v1_C_860007 at http://www.genome.jgi-psf.org/sojae1/sojae1.…”
Section: Phylogeny Of Argonaute-piwi Dicer-like and Rdrp Proteinsmentioning
confidence: 99%